Penerapan ISAK 35 dalam Penyusunan Laporan Keuangan pada Organisasi Nirlaba Pura Sambi Agung Sapto Argo Kecamatan Ngajum Kabupaten Malang - Wukir Janu Anggaluh Loga; Khojanah Hasan; Endah Puspitosarie (CV. Ulil Albab Corp, 2024)
Many entities, whether for profit or not, use accounting extensively in the management of an entity's finances. Statement of Financial Accounting Standards (PSAK) 45 was previously used to regulate non-profit or not-for-profit entities regarding financial reporting. Now, Interpretation of Financial Accounting Standards (ISAK) 35 regulates these entities. The aim of this research is to ascertain how ISAK 35 is applied to the financial reporting of the non-profit organization Pura Sambi Agung Sapto Argo, Ngajum District, Malang Regency. This research method uses a qualitative method with a descriptive approach. The setting in this research is Sambi Agung Saptor Argo Temple, Ngajum District, Malang Regency, which is located at Jl. Mawar, Kesamben Village, Ngajum District, Malang Regency. It can be concluded that Sambi Agung Sapto Argo Temple, Ngajum District, Malang Regency, in presenting its financial reports, has not implemented ISAK 35 as the currently applicable standard.